Theoretical and technical background and clinical considerations for tooth-supported overdentures - ÖZKAN, YASEMİN; GÖZNELİ, RİFAT (Springer Nature, 2023)
The concept of tooth-supported overdenture (TSO) is a cost-effective and straightforward treatment than the implant-supported overdenture (IOD). When a few remaining teeth are present, they can be retained and used as abutments for a TSO to improve retention and stability. The concept of TSO has some advantages for delaying the process of complete edentulism by preserving the bone structure and preventing bone resorption.
Keywords: Diş Hekimliği; Klinik Bilimler; Protetik Diş Tedavisi; Sağlık Bilimleri; Dentistry; Clinical Sciences; Prosthetic Dentistry; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry